2019
DOI: 10.30773/pi.2018.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotional Stability on Insomnia through Anxiety in Patients with Cataracts

Abstract: This study investigated the effect of emotional stability (ES) on insomnia through anxiety in preoperative patients with cataracts. Fifty-four subjects completed a self-questionnaire that included the Insomnia Severity Index (ISI), the International Personality Item Pool (IPIP) for ES, and the Hospital Anxiety and Depression scale (HADS). Pathway analysis was performed to analyze the mediating effects of ES, the anxiety subscale scores of the HADS, and the ISI scores. The low-ES group exhibited an insomnia sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Sociodemographic characteristics of the studied sample: Regarding to age, the present study showed that, the age of the studied groups were ranged between (49-65 years old) and the mean age of the study group was 57.30±5.11 and control group was 58.16±4.97. This finding was consistent with the study done (Ahn, et al, 2019) who stated that the mean age of studied groups was 62.6±10.7 years. Also this finding was in line with (Chawla & Benbadis, 2022) who reported that the age of most of the studied sample was ranged between ranged between 23-65 years old.…”
Section: Discussionsupporting
confidence: 93%
“…Sociodemographic characteristics of the studied sample: Regarding to age, the present study showed that, the age of the studied groups were ranged between (49-65 years old) and the mean age of the study group was 57.30±5.11 and control group was 58.16±4.97. This finding was consistent with the study done (Ahn, et al, 2019) who stated that the mean age of studied groups was 62.6±10.7 years. Also this finding was in line with (Chawla & Benbadis, 2022) who reported that the age of most of the studied sample was ranged between ranged between 23-65 years old.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that low emotional stability was the influencing factor on the BAI score and was consistent with Akram et al [ 15 ], Ahn et al [ 16 ], and Ahmed et al [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Anxiety was a mediator of emotional stability. Ahn et al [ 16 ] studied the relationship and said that low emotional stability would affect sleep and was mediated by anxiety. Ahmed et al [ 17 ] outlined that anxiety was not significantly related to gender and age, but was negatively and significantly correlated to emotional stability.…”
Section: Introductionmentioning
confidence: 99%
“…With that in mind, research has evidenced the relationship between particular personality traits (i.e. Perfectionism, emotional stability) and insomnia symptoms to be mediated by anxiety and depression (Ahn et al., 2019; Akram et al., 2017; Batterham et al., 2012; Jansson-Fröjmark and Linton, 2007).…”
Section: Introductionmentioning
confidence: 99%